ANALISIS SISA HASIL USAHA (SHU) KOPERASI DI INDONESIA MENGGUNAKAN REGRESI DATA PANEL - VANESSA ANGELICA HERIYANTO; I GUSTI AYU MADE SRINADI; DESAK PUTU EKA NILAKUSMAWATI (E-Jurnal Matematika, 2026)
Cooperatives are a vital pillar of the Indonesian economy aimed at improving member welfare, as reflected in the Surplus of Operations (SHU). This study aims to analyze the influence of the number of members, equity, business volume, and external capital on the SHU of Indonesian cooperatives at the provincial level from 2017 to 2023. Given the potential for multicollinearity among independent variables, the research method employs panel data regression analysis integrated with a Ridge Regression approach to produce more stable parameter estimates. The models estimated include the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with the best model selected using the Chow and Hausman tests. To ensure estimation accuracy against heteroskedasticity and autocorrelation, this study applies the Robust Standard Error procedure. The results show that the Fixed Effect Model (FEM) with individual effects integrated with Ridge Regression is selected as the best model, yielding an R-squared value of 88.45%. The analysis reveals that equity and business volume have a significant effect on SHU.